Day-to-day friends’ victimization, aggression perpetration, and morning cortisol activity in late adolescents - Arbel, Reout (Dev Psychobiol, 2019)
This study investigates bi-directional associations between adolescents’ daily experiences of victimization and aggression perpetration within friendships. We investigated a) across-day associations between victimization and aggression perpetration; b) morning cortisol activity as a moderator of cross-day victimization and aggression links; and c) potential sex differences in these patterns. For four consecutive days, 99 adolescents (M(age)= 18.06, SD= 1.09, 46 females) reported whether they were victimized by or aggressive toward their friends. On three of these days, adolescents provided three morning saliva samples. Multilevel path analyses showed that across days, victimization and aggression were bi-directionally linked, but only for male adolescents. Additionally, for male adolescents, morning cortisol output (but not morning cortisol increase) moderated the association between victimization and next-day aggression; victimization predicted greater next-day aggression for boys with low, but not high, morning cortisol output. Findings implicate a physiological factor that may modify daily links between victimization and aggression in male adolescent friendships.